KEY DRIVERS FOR THE GREAT PATHWAY TO SUSTAINABLE BUSINESS: A MULTIDIMENSIONAL FRAMEWORK - Didi Sundiman; Fatma Satyani (Lembaga Penelitian dan Pengabdian kepada Masyarakat - Universitas Universal., 2025)
This research aims to provide a comprehensive understanding of the pathways to business sustainability by recognizing the growth of Knowledge Management and Sustainable Supply Chains, the study aims to identify key trends and intellectual structures in this field. Employing a qualitative approach, the research utilizes content analysis on a sample of 48 prior research studies from reputable academic databases. The AI tool notebookLM aided in the organization and thematic analysis of the data. The findings reveal that achieving enduring business sustainability requires a multifaceted approach encompassing six interconnected factors. These include the strategic integration of sustainability into core business strategy and purpose, often guided by the triple bottom line; the implementation of sustainable operations and supply chain management, including developing a green supply chain; the establishment of effective performance measurement and reporting of sustainability using relevant performance indicators; the fostering of knowledge and innovation for sustainability through effective knowledge management; meaningful stakeholder engagement and collaboration considering stakeholder value; and the development of organizational capacity and adaptation for sustainability, including business model adaptation. These elements collectively enable organizations to navigate the complexities of achieving a truly sustainable business model and drive long-term value creation.